Pendidikan Tata Rias Pengantin (Studi Situs Pengelolaan pada LKP Moncar Surakarta) - Indriastuti, Wahyu Ari; Sarjono, Yetty; Sutrisno, Budi (Universitas Muhammadiyah Surakarta, 2013)
This research aimed to describe characteristics of (1) education planning; (2) education organizing; (3) education implementation; (4) education evaluation; and (5) supporting and inhibiting factors for education bridal makeup at LKP Mon- car. Type of research is a qualitative with an ethnographic approach. Implementation research in LKP Moncar Surakarta. Informants were chosen are the owner of LKP Moncar, learners, instructure. The validity of the data using source triangulation tech- niques and triangulation method. The conclusions of this research are characteristics of education bridal makeup in LKP Moncar Surakarta (1) education planning through ideas, acceptance of new students, and preparing educational bridal makeup materials are arranged in the form of Teaching Education (Unit Satuan Ajar Pendidikan/ SAP); education organizing done by placing instructors to handle incoming new students and handling facility management skills institutions, infrastructure, media learning and personnel and the distribution of skill levels of learners to all instructors and organize training agenda and organize training agenda and competition schedules based on each competition to the instructor; (3) education implementation in are procurement, usage, maintenance, and removal of owned skills institutions and achievement social- ization to new students also move instructors to carry out activities to achieve the target graduation; (4) education evaluation is done through planning and implementa- tion of admission new students and refers to skills attainment, graduation rates, and acquisition grades of student while monitoring the performance of team success; and (5) Factors supporting education at LKP Moncar is the support of family (husband and children), cost of teaching and learning needs is low, learning facilities bridal makeup does not always use the media and certain brands, and inhibiting factor for education is the difficulty of obtaining student.